Pengaruh Kualitas Guru Terhadap Sistem Pembelajaran Kelas 1 & 2 di SDN Cigendel - Farida, Rike Nur; Nurjanah , Mia Astri (Program Studi Akuntansi IKOPIN, 2022)
You can feel for yourself that the current learning system cannot be said to be good, there are still many problems that occur in the world of education. One of the causes of the low learning system in Indonesia is the quality of teachers. The results of the UKG or Teacher Competency Test from 2012 to 2015, around 81% of teachers in Indonesia did not even reach the minimum score. This study aims to determine the effect of teacher quality on the learning system at SDN Cigendel. The analytical method used in this study is a quanitative descriptive method that uses data collection such as in interview and questionnaire (questionnaire). Based on the results of the study: The quality of teachers is influenced by the role of teachers on the learning system in students, the lack of teacher role in the learning process due to face-to-face learning time is reduced from the normal time of 3 hours of learning to only 1 hour of learning. While all materials are not fully conveyed, especially in odd semesters where the distance learning process is applied. Not only that, there are also many factors that hinder in the efforts of teachers to launch literacy and numerization. This makes it difficult for students in terms of literacy and numerization. Therefore, teachers must be able to streamline the time they have so that the material is delivered and students can be fluent in literacy and numerization.